2015
DOI: 10.2135/cropsci2014.08.0569
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Allele at the Rsv3 Locus for Resistance to Soybean Mosaic Virus in PI 61944 Soybean Accession

Abstract: Soybean mosaic virus (SMV) is a prevalent pathogen in soybean [Glycine max, (L.) Merr.]. Several SMV resistance genes have been discovered, but most of them do not provide resistance to all strains of SMV. The objective of this research was to identify new genes or alleles displaying differential reactions to SMV strains in the SMV‐resistant soybean genotype, PI 61944. Cross combinations were made to develop F2 and F2:3 populations, followed by mapping analyses and greenhouse screenings using G1 and G7 virus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Rsv3 alleles with differential responses to SMV strains have been identified in PI61947 (Rsv3-h) and PI399091 (Rsv3-c) (Shakiba et al, 2012a). Cervantes-Martinez et al (2015) identified a new Rsv3 allele, Rsv3-n, in PI61944. Other soybean cultivars, PI91346, Tej-sen-daaj-pi and Kolhida 4, contain new but as yet uncharacterized Rsv3 alleles .…”
Section: Resistance Genes Of the Smv Pathosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Rsv3 alleles with differential responses to SMV strains have been identified in PI61947 (Rsv3-h) and PI399091 (Rsv3-c) (Shakiba et al, 2012a). Cervantes-Martinez et al (2015) identified a new Rsv3 allele, Rsv3-n, in PI61944. Other soybean cultivars, PI91346, Tej-sen-daaj-pi and Kolhida 4, contain new but as yet uncharacterized Rsv3 alleles .…”
Section: Resistance Genes Of the Smv Pathosystemmentioning
confidence: 99%
“…Cervantes‐Martinez et al . () identified a new Rsv3 allele, Rsv3‐n , in PI61944. Other soybean cultivars, PI91346, Tej‐sen‐da‐aj‐pi and Kolhida 4, contain new but as yet uncharacterized Rsv3 alleles (Li D. et al ., ).…”
Section: Resistance Genes Of the Smv Pathosystemmentioning
confidence: 99%
“…Therefore, the chance for the occurrence of a superior SMV isolate that can overcome all resistance genes is extremely low, and pyramiding R genes may be a sound option. Indeed, the pyramiding of three R-genes using marker-assisted selection (MAS) has been reported, and potential lines may be released to support breeding programs [61,64,89,113].…”
Section: Smv Resistance Genesmentioning
confidence: 99%
“…The Rsv1 locus includes at least ten alleles (Chen et al, 1991, 2001, 2002; Kiihl and Hartwig, 1979; Roane et al, 1983; Shakiba et al, 2013) and generally confers resistance to less virulent strains (G1–G4) and susceptibility or necrosis to more virulent strains (G5–G7) (Table 1) (Chen et al, 1991; Gunduz et al, 2002; Ma et al, 2002; Li et al, 2010). The Rsv3 locus contains at least six alleles (Buzzell and Tu, 1989; Gunduz et al, 2001; Cervantes‐Martinez et al, 2015; Shakiba et al, 2012) and confers resistance to more virulent strains (G5–G7) and susceptibility to less virulent strains (G1–G4) (Table 1). The Rsv4 locus has at least three alleles conferring resistance to all or most strains (G1–G7) (Buss et al, 1997; Ma et al, 2002; Gunduz et al, 2004; Shakiba et al, 2013); however, often shows resistance at early vegetative stage and delayed mild susceptibility at a later stage (Table 1) (Buss et al, 1997; Gunduz et al, 2004)…”
Section: Reactions Of Soybean Genotypes Carrying Single R‐genes To Sementioning
confidence: 99%
“…necrosis to more virulent strains (G5-G7) (Table 1) (Chen et al, 1991;Gunduz et al, 2002;Ma et al, 2002;Li et al, 2010). The Rsv3 locus contains at least six alleles (Buzzell and Tu, 1989;Gunduz et al, 2001;Cervantes-Martinez et al, 2015;Shakiba et al, 2012) and confers resistance to more virulent strains (G5-G7) and susceptibility to less virulent strains (G1-G4) (Table 1). The Rsv4 locus has at least three alleles conferring resistance to all or most strains (G1-G7) (Buss et al, 1997;Ma et al, 2002;Gunduz et al, 2004;Shakiba et al, 2013); however, often shows resistance at early vegetative stage and delayed mild susceptibility at a later stage (Table 1) (Buss et al, 1997;Gunduz et al, 2004) To understand the principles of SMV infection and identify genetic sources of resistance, extensive genetic studies need to be conducted.…”
mentioning
confidence: 99%